2008
DOI: 10.1513/pats.200706-080et
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life in Emphysema

Abstract: Patients with emphysema may experience reduced health-related quality of life (HRQOL). HRQOL measures have evolved from two different measurement traditions: psychometric theory and decision theory. Psychometric methods typically create a profile of outcomes, whereas decision theory methods offer a summary score on a continuum ranging from 0.0 (for death or worst possible health) to 1.0 (for best possible health). Decision theory methods are better suited for cost-effectiveness studies. Generic HRQOL measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…It measures HRQOL from a 'decision theory approach,' in which differently weighted symptoms contribute to one final score, which can be applied to any population. 46 This is distinct from the approaches of other QOL instruments, in which a profile is generated composed of measurements in several domains; the QWB correlated only moderately to the physical domain of the psychometric SF-36 instrument. 5 The QWB tells health-care providers very little about the HRQOL of their individual SCI client, as it is intended to offer interpopulation comparison, with less sensitivity to clinical change.…”
Section: Measurement Properties Of Instrumentsmentioning
confidence: 89%
See 1 more Smart Citation
“…It measures HRQOL from a 'decision theory approach,' in which differently weighted symptoms contribute to one final score, which can be applied to any population. 46 This is distinct from the approaches of other QOL instruments, in which a profile is generated composed of measurements in several domains; the QWB correlated only moderately to the physical domain of the psychometric SF-36 instrument. 5 The QWB tells health-care providers very little about the HRQOL of their individual SCI client, as it is intended to offer interpopulation comparison, with less sensitivity to clinical change.…”
Section: Measurement Properties Of Instrumentsmentioning
confidence: 89%
“…5 The QWB tells health-care providers very little about the HRQOL of their individual SCI client, as it is intended to offer interpopulation comparison, with less sensitivity to clinical change. 46 With respect to the SWLS, it is possible that the brevity and generality of its approach, as well as the wording of several of the questions (for example 'If I could live my life over, I would change almost nothing'), weaken its applicability with SCI population.…”
Section: Measurement Properties Of Instrumentsmentioning
confidence: 99%
“…The prevalence of depression in older adults in the general population has been estimated as between 8 and 20%; thus studies to date clearly indicate higher depression rates among patients with COPD (21). Multiple studies have also demonstrated poor quality of life among patients with COPD (22), and this was explored in greater detail by Kaplan and Ries (see pages 561-566 of this symposium [32]). …”
Section: Cognitive Deficits and Psychological Difficulties In Chronicmentioning
confidence: 99%
“…9 Both end-stage lung disease (ESLD) and OSA have been associated with decreased health-related quality of life (HRQOL) and important comorbidities. [10][11][12] If the rate of OSA in ESLD patients is substantial, some of the associated changes in HRQOL and comorbidities could be due to the presence of concomitant OSA. In view of the scarcity of data on the case rate of OSA in patients with ESLD and a possible association between OSA and multiple comorbidities as well as poor HRQOL, we performed a retrospective review of patients with ESLD referred to our lung transplant service for evaluation.…”
mentioning
confidence: 99%